Avelumab, a PD‐L1 Inhibitor, in Combination with Hypofractionated Radiotherapy and the Abscopal Effect in Relapsed Refractory Multiple Myeloma. (10th March 2021) - Kazandjian, Dickran; Dew, Alexander; Hill, Elizabeth; Ramirez, Elizabeth Gil; Morrison, Candis; Mena, Esther; Lindenberg, Liza; Yuan, Constance; Maric, Irina; Wang, Hao‐Wei; Calvo, Katherine; Dulau‐Florea, Alina; et al.
Abstract: Lessons Learned: Despite the initial optimism for using immune checkpoint inhibition in the treatment of multiple myeloma, subsequent clinical studies have been disappointing. Preclinical studies have suggested that priming the immune system with various modalities in addition to checkpoint inhibition may overcome the relative T‐cell exhaustion or senescence; however, in this small data set, radiotherapy with checkpoint inhibition did not appear to activate the antitumor immune response. Background: Extramedullary disease (EMD) is recognized as an aggressive subentity of multiple myeloma (MM) with a need for novel therapeutic approaches. We therefore designed a proof‐of‐principle pilot study to evaluate the synergy between the combination of the anti–PD‐L1, avelumab, and concomitant hypofractionated radiotherapy. Methods: This was a single‐arm phase II Simon two‐stage single center study that was prematurely terminated because of the COVID‐19 pandemic after enrolling four patients. Key eligibility included patients with relapsed/refractory multiple myeloma (RRMM) who had exhausted or were not candidates for standard therapy and had at least one lesion amenable to radiotherapy. Patients received avelumab until progression or intolerable toxicity and hypofractionated radiotherapy to a focal lesion in cycle 2. Radiotherapy was delayed until cycle 2 to allow the avelumab to reach a study state, given the important observation from previous studies that concomitant therapy is needed for the abscopal effect. Results: At a median potential follow‐up of 10.5 months, there were no objective responses, one minimal response, and two stable disease as best response. The median progression‐free survival (PFS) was 5.3 months (95% confidence interval [CI]: 2.5–7.1 months), and no deaths occurred. There were no grade ≥3 and five grade 1–2 treatment‐related adverse events. Conclusion: Avelumab in combination with radiotherapy for patients with RRMM and EMD was associated with very modest systemic clinical benefit; however, patients did benefit as usual from local radiotherapy. Furthermore, the combination was very well tolerated compared with historical RRMM treatment regimens.